2009
DOI: 10.1038/ajh.2009.35
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment Is Related to Increased Arterial Stiffness and Microvascular Damage in Patients With Never-Treated Essential Hypertension

Abstract: Impaired cognitive function is associated with increased large artery stiffness and microalbumin excretion in newly diagnosed, untreated hypertensive patients. These findings support the hypothesis that cognitive impairment induced by impaired microcirculation is linked to large artery stiffness and microvascular damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 39 publications
(31 reference statements)
1
53
1
1
Order By: Relevance
“…These mechanisms are known to be adversely associated both with LV function10, 11 and cognition12, 13; thus, observed associations between LV function and cognition may be confounded by “common causes.” Understanding these pathways is essential to identifying cardiac targets that may delay or prevent cognitive decline and dementia.…”
Section: Introductionmentioning
confidence: 99%
“…These mechanisms are known to be adversely associated both with LV function10, 11 and cognition12, 13; thus, observed associations between LV function and cognition may be confounded by “common causes.” Understanding these pathways is essential to identifying cardiac targets that may delay or prevent cognitive decline and dementia.…”
Section: Introductionmentioning
confidence: 99%
“…22,23,25,27,81 Several large populationbased studies document an association between increased arterial stiffness (AS) and impaired cognitive function in elderly patients with known vascular dementia, 82 mild cognitive impairment, 83 and memory loss, 24 as well as in otherwise healthy subjects. 25 Specifically, cross-sectional observations documenting the association between increased arterial stiffness and cognitive performance report significant deficits in memory, 24,25 psychomotor speed, 22,25 global cognitive function (mini mental state examination score), 23,26 and increased prevalence and severity of white matter hyperintensities (WMH: suggestive of ischemic changes). 24 In a longitudinal study, over a 2-year span in individuals without dementia who had no history of cerebral vascular or renal disease, higher baseline pulse pressure, and pulse wave velocity was associated with an accelerated rate of decline in verbal and non-verbal memory, attention, and concentration capacities.…”
Section: 75mentioning
confidence: 99%
“…23 Although the majority of work has been reported in populations with specific co-morbid conditions, such as hypertension or diabetes mellitus, there is evidence that cognitive dysfunction may be present in overtly asymptomatic populations due to sub-clinical vascular remodeling. In addition to changes in vascular morphology with chronic diseases and conditions, arterial stiffness increases with aging 22,26 and sub-clinical changes in vascular morphology has been implicated in the age-associated change in cognitive function. 22 Thus, persistently elevated HR documented in individuals with paraplegia may predispose these individuals to premature arterial stiffness 78,79,84 and accelerated age-associated declines in cognitive function.…”
Section: 75mentioning
confidence: 99%
See 1 more Smart Citation
“…Many investigations have suggested that arterial stiffness is a predictor and risk factor of cognitive impairment and dementia [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] . The aim of this study is to review the relationship between arterial stiffness and cognitive impairment in neurodegenerative diseases including Alzheimer's disease (AD) and Parkinson's disease (PD).…”
Section: Introductionmentioning
confidence: 99%